The analysis of code switching and code mixing in the ‘Historytelling’ YouTube segment by Nessie Judge - Ajeng Anditya Putri Nugroho; Izzati Gemi Seinsiani (ELT Forum: Journal of English Language Teaching, 2025)
In recent years, the growth of digital platforms has significantly affected the linguistic practices of the youth, especially in multilingual societies. An important linguistic phenomenon that has emerged in this context is the frequent use of code-switching and code-mixing, especially by online content creators. While many studies have examined these phenomena in everyday conversation and educational contexts, limited focus has been given to their application in educational and entertainment content on YouTube. This study aims to fill the gap by analyzing the types, functions, and factors influencing code-switching and code-mixing in ten selected episodes of the ‘Historytelling’ segment by Nessie Judge, a well-known Indonesian YouTuber. A descriptive qualitative method was employed, using Poplack's (1980) and Muysken's (2000) typologies to classify linguistic features, while communicative functions and motivational factors were interpreted using Marasigan's (1983) and Hoffman's (1991) frameworks. The results showed that inter-sentential switching and insertion mixing are the most frequently used types, which serve certain communicative purposes such as message qualification, addressee specification, and facility of expression. The analysis also showed that the most important influencing factor was talking about particular topic, especially when English terms are preferred due to historical accuracy. Nessie's language choices appear consciously and audience-oriented, reflecting digital youth culture and the pedagogical potential of bilingual content. This research concludes that Nessie Judge's strategic bilingualism increases the accessibility, engagement, and educational value of content. The implications suggest that code-switching and code-mixing, when used purposefully, can be powerful tools in digital pedagogy and sociolinguistic engagement, especially for Gen Z audiences that navigate multilingual realities in online spaces.